Role of oxygen vacancies in the magnetic and dielectric properties of the high-dielectric-constant system CaCu3Ti4O12: An electron-spin resonance study - Pires, M. A.; Israel, C.; Iwamoto, W.; Urbano, R. R.; Aguero, O.; Torriani, I; Rettori, C.; Pagliuso, P. G.; Walmsley, L.; Le, Z.; Cohn, J. L.; Oseroff, S. B. (American Physical Soc, 2006)
We report experiments of electron spin resonance (ESR) of Cu2+ in polycrystalline samples of CaCu3Ti4O12 post-annealed in different atmospheres. After being synthesized by solid state reaction, pellets of CaCu3Ti4O12 were annealed for 24 h at 1000 degrees C under air, Ar or O-2. Our temperature dependent ESR data revealed for all samples nearly temperature independent g value (2.15(1)) and linewidth for T > T-N approximate to 25 K. However, the values of ESR linewidth are strongly affected by the oxygen content in the sample. For instance, argon post-annealed samples show a much larger linewidth than the O-2 or air post-annealed samples. We attribute this broadening to an increase of the dipolar homogeneous broadening of the Cu2+ ESR lines due to the presence of oxygen vacancies which induce an S=1/2 spin inside the TiO6 octahedra. Correlation between a systematic dependence of the ESR linewidth on the oxygen content and the high dielectric constant of these materials is addressed. Also, ESR, magnetic susceptibility, and specific heat data for a single crystal of CaCu3Ti4O12 and for polycrystals of CdCu3Ti4O12 are reported.